THE ROLE OF PRODUCT INNOVATION AS A STRATEGY TO INCREASE UMKM SALES AT CV ISEKAI AUTO CLEANER - Abdul Aziz; Abdul Husenudin; Laeli Junaedi; Muhammad Agil Zan; Muhammad Ibnu Aqil; Nadia Putri Utami Diets; Putri; Siti Munazilah (Journal Informatic, Education and Management (JIEM), 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the Indonesian economy; however, they are faced with increasingly intense competition, particularly in the cleaning products and services sector. This condition requires business actors to implement adaptive strategies, one of which is product innovation. This study aims to analyze the role of product innovation as a strategy to increase sales at the MSME CV Isekai Auto Cleaner. The research employs a qualitative approach using a case study method. Data were collected through interviews, observations, and documentation, and then analyzed using descriptive qualitative analysis with triangulation techniques. The results show that CV Isekai Auto Cleaner implements innovation through improving service quality, using more modern equipment, developing a wider range of services, and presenting products in a more attractive manner that aligns with consumer needs. These innovations have a positive impact on customer interest and satisfaction, as reflected in repeat purchases, recommendations, and increased sales. The findings confirm that innovation does not have to be large-scale; improvements to existing services, when aligned with market needs, are capable of enhancing the competitiveness and sustainability of MSMEs.